2006
DOI: 10.1021/bi060983y
|View full text |Cite
|
Sign up to set email alerts
|

Heterochromatin Protein 2 Interacts with Nap-1 and NURF:  A Link between Heterochromatin-Induced Gene Silencing and the Chromatin Remodeling Machinery in Drosophila

Abstract: Heterochromatin Protein 2 is a nonhistone chromosomal protein from Drosophila melanogaster that binds to HP1 and has been implicated in heterochromatin-induced gene silencing. Heretofore, HP1 has been the only known binding partner of HP2, a large protein devoid of sequence motifs other than a pair of AT-hooks. In an effort to identify proteins that interact with HP2 and assign functions to its various domains, nuclear proteins were fractionated under non-denaturing conditions. On separation of nuclear protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 41 publications
(71 reference statements)
1
12
0
Order By: Relevance
“…Notably, an intrinsic transcriptional repression function was observed when NAP1 was tethered to DNA. In line with this observation, very recently findings revealed that NAP1 is associated with the heterochromatic protein 2, HP2, in Drosophila, suggesting that NAP1 is in part associated with heterochromatin (35). Whether this is a direct cause through nucleosome deposition or is mediated by other interacting proteins has to be investigated.…”
Section: Discussionmentioning
confidence: 83%
“…Notably, an intrinsic transcriptional repression function was observed when NAP1 was tethered to DNA. In line with this observation, very recently findings revealed that NAP1 is associated with the heterochromatic protein 2, HP2, in Drosophila, suggesting that NAP1 is in part associated with heterochromatin (35). Whether this is a direct cause through nucleosome deposition or is mediated by other interacting proteins has to be investigated.…”
Section: Discussionmentioning
confidence: 83%
“…The Nap1-null mutant allele is homozygous-lethal (Stephens et al 2006), whereas Nlp/Nph and P32 are not. To better understand interactions among protamine chaperones in vivo, we combined Nlp/Nph and P32 mutations and discovered significant recessive and dominant interactions (Table 2).…”
Section: Histone Chaperone Activity Of Tap/p32mentioning
confidence: 99%
“…ACF has also been shown to bind directly to the Drosophila HP-1 variant dHP-1a, and aid its loading to chromatin [14]. A recent report shows a physical interaction of the NuRF complex with the heterochromatin protein dHP-2, although the NURF301 subunit failed to show any genetic effect on heterochromatin formation [15]. Finally, purification of a complex containing the methyltransferase Clr3 from Schizosaccharomyces pombe revealed the presence of the Mit1 protein, whose chromatin remodelling activity was necessary for heterochromatin formation [16].…”
Section: Introductionmentioning
confidence: 99%